POLICY, SOCIAL-ECONOMIC, AND INSTITUTIONAL CONTEXT IN PEATLAND MANAGEMENT IN INDONESIA - Sujianto, Sujianto; Zulkarnaini, Zulkarnaini; Nasution, Mimin Sundari (International Conference On Social Science Education, 2023)
This paper describes the dynamics that occur in the use and management of peatlands in Indonesia as a result of various policies that are not integrated. Various policies have been made by the government in an effort to use and manage peatlands properly. The problem is that many of these policies are accused of being motivated by short-term interests that override long-term considerations. This study uses a legal policy approach, which is an approach that is carried out by observing laws and regulations relating to the policy issues under study. The results of the study show that the dynamics of peatland policies in Indonesia, which experience ups and downs, clearly show a paradoxical position, namely the existence of policy variables that emphasize the value of sustainability and variables that prioritize the value of development. The fires and haze that often occur in the dry season and the accompanying diseases in many areas are an unavoidable impact due to errors in peatland utilization and management policies.